The AN69 ST haemodialysis membrane under conditions of two different extracorporeal circuit rinse protocols a comparison of thrombogenicity parameters - Richtrová, Pavlína; Opatrný, Karel; Vít, Ladislav; Šefrna, František; Perlík, Radek (Nephrology, dialysis, transplantation, 2007)
BACKGROUND: Thrombogenicity is an important parameter of haemodialysis (HD) membrane biocompatibility. The surface of the polyacrylonitrile AN69 ST membrane is coated with a polyethylenimine. This modification allows heparin adsorption. The binding of heparin to the membrane surface occurs during priming of the extracorporeal circuit (ECC) by rinsing it with saline and heparin. Our aims were to assess and compare the thrombogenicity of the AN69 ST membrane under conditions of two extracorporeal circuit (ECC) rinse protocols-with and without unfractionated heparin (UFH). METHODS: In a prospective, crossover and randomized study, we examined 10 patients during HD after ECC preparation with either rinse protocols. Prior to HD and at 15, 60 and 240 min, we determined plasma levels of the thrombin-antithrombin complexes (TAT), platelet factor 4 (PF4), heparin concentration (antiXa) and thrombocyte count. Systemic anticoagulation was performed using UFH. RESULTS: During HD after ECC rinse without UFH, there was a significantly earlier and more marked increase in TAT compared with UFH-containing rinse (P <0.05). Using Spearman coefficient, we demonstrated a significant correlation between TAT and antiXa at 60 min (r = -0.534) and 240 min (r = -0.538). A comparison of the TAT/antiXa ratios between rinses at 60 min revealed a significantly higher increase in TAT following UFH-free rinse (P <0.05). There was no difference in PF4 between the rinses. Platelet count did not change significantly during HD using either rinse protocol. CONCLUSION: Based on plasma TAT levels, ECC priming with an UFH-containing solution reduces the thrombogenicity of the AN69 ST membrane. There is no significant difference between both types of priming concerning PF4 and thrombocyte count.
Keywords: akrylové pryskyřice; Sensitivity and Specificity; senzitivita a specificita; klinické křížové studie; Humans; lidé středního věku; hemodialyzační roztoky; Renal Dialysis; Equipment Design; Female; Aged; Platelet Factor 4; trombocyty; Hemodialysis Solutions; financování organizované; dialýza ledvin; Financing, Organized; senioři; lidé; Thrombosis; heparin; randomizované kontrolované studie jako téma; reprodukovatelnost výsledků; časové faktory; Acrylic Resins; Biocompatible Materials; Blood Platelets; Heparin; Adsorption; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Randomized Controlled Trials as Topic; design vybavení; trombóza; trombocytový faktor 4; biokompatibilní materiály; Cross-Over Studies; adsorpce; mužské pohlaví; prospektivní studie; Time Factors; Prospective Studies